Discovery of a Phenylalanine-derived Natural Compound as a Potential Dual Inhibitor of MDM2 and MDMX - Cho, Ja Young; Park, Sanghwa; Kim, Taejung; Eom, Junghye; Rho, Jung-Rae; Bai, Hyoung-Woo (Wiley - V C H Verlag GmbbH & Co., 2025)
Dual inhibition of the negative p53 regulators MDM2 and MDMX has emerged as an effective strategy in p53-based anticancer therapy. However, dual inhibitors are limited, and many inhibitors exhibit poor pharmacokinetic properties and fast dissociation kinetics. Among newly identified microbial metabolites, the novel phenylalanine-derived compound P5 isolated from Micromonospora sp. MS-62 (FBCC-B8445) exhibited inhibitory activity against both MDM2 and MDMX. The binding of P5 to MDM2 and MDMX was demonstrated by surface plasmon resonance, which revealed nanomolar-level affinity and slow dissociation kinetics (KD = 46？nM for MDM2; 576？nM for MDMX). This dual inhibitory activity was further supported by molecular docking, which revealed binding of P5 to the p53-binding pockets of both MDM2 and MDMX through extensive non-covalent interactions. In cell-based assays, P5 reduced cancer cell viability across several human cell lines. Furthermore, in silico analysis indicated favorable pharmacokinetic properties, including gastrointestinal absorption, blood？brain barrier permeability, and compliance with Lipinski’s and Veber’s criteria. P5 combines dual-target engagement with binding persistence and favorable pharmacokinetic characteristics, addressing limitations of earlier inhibitors. P5 is a potential lead compound for the development of MDM2/MDMX-targeted anticancer agents.